The Volunteering teaching in an early childhood education center of a federal university - Rassele Soprani, Maria Jose; Nazaré de Andrade Ferreira, Dirce; Soprani, Arildo; Zanette Nascimento, Luiz Cláudio; Corrêa da Silva, Marina (Guará Journal, 2017)
This article deals with the provision of volunteer teaching service in a child education unit that has the peculiarity of functioning in a federal public university, receiving the denomination of "university day care". The institution since the 1970s has developed a complex voluntary work that shows its importance both for the institution itself and for the public that receives the service. However, from the point of view of service providers, there are important aspects that need to be unveiled, since it is a kind of work that involves dedication, selflessness and lack of perspective regarding the labor bond. In this context, this article aims to present the peculiarities and the perception of the volunteers about the service provided. To uncover particularities about the subject, we used bibliographic, exploratory, descriptive research and semi-structured interviews.